1981
DOI: 10.1530/jrf.0.0630001
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod induction of fertile oestrus and changes in LH and progesterone concentrations in yearling dairy goats (Capra hircus)

Abstract: Oestrus and ovulation were induced in a group of 19 yearling dairy goats which had been maintained for 70 days on a 19 h/day photoperiod regimen. Six yearling females, raised under natural photoperiod, served as controls. An intact, light-treated male was introduced to each group 42 days after termination of the artificial lighting. Behavioural, endocrine and kidding observations indicated that 15 of the experimental females (79%) ovulated within 21-30 days after introduction of the male, that 12 (63%) conceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
3

Year Published

1984
1984
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 12 publications
3
9
0
3
Order By: Relevance
“…Asher et al (1988a) reported that, in fallow deer, the duration of the LH surge extended over approximately 15 h. Thus, in these three species of deer, the LH surge exhibits a similar dynamic change following progesterone decline. In this respect, deer would appear to exhibit a longer LH surge than those reported for cattle (Rahe et al, 1980;Peters, 1984;Walters & Schallenberger, 1984) or goats (BonDurant, 1981) but similar to that for sheep (McLeod et al, 1982(McLeod et al, , 1983McLeod & Haresign, 1984).…”
Section: Discussionsupporting
confidence: 58%
“…Asher et al (1988a) reported that, in fallow deer, the duration of the LH surge extended over approximately 15 h. Thus, in these three species of deer, the LH surge exhibits a similar dynamic change following progesterone decline. In this respect, deer would appear to exhibit a longer LH surge than those reported for cattle (Rahe et al, 1980;Peters, 1984;Walters & Schallenberger, 1984) or goats (BonDurant, 1981) but similar to that for sheep (McLeod et al, 1982(McLeod et al, , 1983McLeod & Haresign, 1984).…”
Section: Discussionsupporting
confidence: 58%
“…In most instances, these increases in progesterone only last 1-3 days and attain a maximum of about 1 ng/ml. Transient, low-amplitude increases in progesterone have also been observed before the first cycle at puberty in lambs (Foster & Ryan, 1979;Berardinelli et al, 1980;Keisler et ai, 1983;Foster et al, 1986), heifers (González-Padilla et al, 1975) and primates (Dierschke et al, 1974;Foster, 1977), after pulsatile administration of GnRH to anoestrous ewes (Legan et al, 1985a;Hunter et ai, 1986), after a ram-induced LH surge in anoestrous ewes (Pearce et al, 1985), at the end of post-partum anoestrus in cows (Pope et ai, 1969), and at onset of the breeding season in dairy goats (BonDurant et al, 1981). They are therefore a common phenomenon of the initiation of cyclicity in at least these 4 species.…”
Section: Methodsmentioning
confidence: 99%
“…Also, photoperiod manipulation [2] and sudden introduction of males [14] induced estrus during the non-breeding season in goats. Pregnancy rates as high as 40-60% have been attained out of breeding season [7], and administration of equine chorionic gonadotropin has been shown to be necessary to get a satisfactory ovulatory response in anestrous goats [10].…”
mentioning
confidence: 99%